Preparations for the Forthcoming Redefinition of the Kilogram. (December 2014) - Davidson, Stuart; Robinson, Ian A
In the next few years, the world's measurement system, the SI, will be changing. One of the most significant changes will be the replacement of the existing definition of the kilogram, which depends on the stability of an artefact made in the 19th century, with a definition based on a constant, the Planck constant h, which lies at the heart of modern quantum physics. This change will strengthen, stabilise and reunify the SI and, in addition, provide advantages to science and engineering. This paper describes the reasons for the change, the innovations which have enabled the change to be made and the efforts to ensure that the transition to the new definition is as problem-free as possible.